2006
DOI: 10.1210/en.2005-1007
|View full text |Cite
|
Sign up to set email alerts
|

Taurine (2-Aminoethanesulfonic Acid) Deficiency Creates a Vicious Circle Promoting Obesity

Abstract: The relation between blood taurine (2-aminoethanesulfonic acid) concentrations and obesity was investigated. Taurine is supplied to the body by dietary ingestion as well as by de novo synthesis; it is anabolized by cysteine dioxygenase (CDO), which is abundantly expressed in liver and white adipose tissue. Overexpression of CDO in 3T3-L1 preadipocytes caused a decrease in the level of cysteine (precursor of taurine) and an increase in the level of taurine in the culture medium, suggesting that CDO is involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
139
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(159 citation statements)
references
References 28 publications
(32 reference statements)
14
139
1
1
Order By: Relevance
“…29 Additionally, a recent study found dietary taurine supplementation to prevent obesity in mice by increased resting energy expenditure. 30 Further studies are needed to examine possible mechanisms. In addition, closer investigation of the effects of portion size and more frequent fish consumption as part of a varied and balanced diet is required.…”
Section: Discussionmentioning
confidence: 99%
“…29 Additionally, a recent study found dietary taurine supplementation to prevent obesity in mice by increased resting energy expenditure. 30 Further studies are needed to examine possible mechanisms. In addition, closer investigation of the effects of portion size and more frequent fish consumption as part of a varied and balanced diet is required.…”
Section: Discussionmentioning
confidence: 99%
“…Ornithine, an intermediate of urea cycle, was elevated in obese women suggesting that they might have abnormal hepatic urea synthesis [11,18]. Taurine supplementation to obese subjects can effectively increase fatty acid oxidation [20]. Furthermore, high-fat obese rodents have high hepatic taurine content with accompanying hypotaurinemia [18,20].…”
Section: Methodsmentioning
confidence: 99%
“…Taurine supplementation to obese subjects can effectively increase fatty acid oxidation [20]. Furthermore, high-fat obese rodents have high hepatic taurine content with accompanying hypotaurinemia [18,20]. Thus, elevated hepatic taurine is a compensatory mechanism to overcome high-fat supply.…”
Section: Methodsmentioning
confidence: 99%
“…Заболеваемость СД и АГ увеличи-вается с возрастом среди жителей экономически раз-витых стран. У большинства больных СД 2 типа, составляющих около 90% лиц с СД и АГ, отмечается эссенциальная гипертензия [4,5].…”
Section: российский кардиологический журналunclassified